The Personality of a Safety Manager - Rak, Roman; Mesaros, Marian; Porada, Viktor (Communications - Scientific letters of the University of Zilina, 2005)
The main aim of the contribution is to provide a detailed review of the role of the safety manager, and to describe the specific demands of his work when enforcing safety in an institution. Attention is given both to the personal characteristics and professional qualifications necessary for performance of his work, which can be complex but also thankless, and also the psychological influences. From a practical standpoint the authors define the essential personal characteristics for the position of a safety manager, and consider ways and options on how to best select a safety manager when filling this important managerial post in an institution, from the IT environment in businesses and state entities, to professional security organisations.